Active learning of DC circuits: spreading the use of the VISIR remote lab in Argentina - Evangelista, Ignacio (2018)
The VISIR+ Project was launched in 2015 with the objective of spreading the use of the VISIR remote laboratory in Latin America, promoting an enquiry-based approach to teaching and learning on electric and electronic circuits. Within the scope of this project, several didactical implementations were achieved both in Argentina and in Brazil. This article describes the latest implementation of VISIR in a pre-university technical school in Argentina (associated partner of the VISIR+ team) in three Physics courses with students having different background knowledge and interests. A set of activities comprising simulations, remote and hands-on experiments were designed in order to engage students in the learning process. The implementation was assessed in terms of the learning objectives and outcomes. Results showed that VISIR is an effective tool to promote active learning. Moreover, this experience seems highly valuable to encourage the dissemination of VISIR in Argentina